Dense Medium Cyclone Technology to Improve Quality of Coal - Pujotomo, Isworo (Transmisi, 2009)
Chimney emissions of coal-fired plants have a negative impact on the environment, as well as causing disruption to the ecosystem and human health because of the spread of SO2 (sulpur dioxide), ash, Nox (nitrogen oxide) and CO2 (carbon dioxide). Using technology, dense medium cyclone, ash from coal lignite and sulpur reduced from 18.82% to 11.70% and 0.91% to 0.88% Keywords: Decrease ash and sulphur coal